2013
DOI: 10.1186/1472-6920-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Junior Doctor performance: a validation study

Abstract: BackgroundIn recent years, Australia has developed a National Junior Doctor Curriculum Framework that sets out the expected standards and describes areas of performance for junior doctors and through this has allowed a national approach to junior doctor assessment to develop. Given the significance of the judgments made, in terms of patient safety, development of junior doctors, and preventing progression of junior doctors moving to the next stage of training, it is essential to develop and validate assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…We measured doctors’ performance using a four-item clinical performance measurement scale (α = 0.76) adopted from Carr et al (2013) . The scale included items such as ‘clinical assessment and patient management,’ ‘procedural skills,’ and ‘emergency management.’ The doctor’s performance was rated from 1 (performance below the minimum acceptable level) to 5 (performance consistently far exceeded expectations).…”
Section: Methodsmentioning
confidence: 99%
“…We measured doctors’ performance using a four-item clinical performance measurement scale (α = 0.76) adopted from Carr et al (2013) . The scale included items such as ‘clinical assessment and patient management,’ ‘procedural skills,’ and ‘emergency management.’ The doctor’s performance was rated from 1 (performance below the minimum acceptable level) to 5 (performance consistently far exceeded expectations).…”
Section: Methodsmentioning
confidence: 99%
“…In a validation study of the JDAT, we identified a Cronbach Alpha of 0.883 for the 10 item scale and identified that two principal components of junior doctor performance are being assessed rather than the commonly reported three [ 15 ]. Cronbach Alphas were 0.829 for the 6 item ‘Clinical Management subscale’ and 0.834 for the 4 item ‘Communication subscale’, indicating good internal consistency and reliability of the instrument in its entirety and for both subscales.…”
Section: Methodsmentioning
confidence: 99%
“…Comparable evaluations from the past of supervisors who rated trainees’ competencies have made similar observations to those of this current study, as identified in our previous review [ 17 ]. Indeed, another more recent study of a similar Australian junior doctor population also found variation in the domain constructs of what was assessed compared to the domains expected to be assessed [ 29 ]. Moreover, from an Australian perspective, other evaluative research has identified concerns about the assessment of a similar junior doctor population in Australia [ 30 32 ], with observations indicating “that the tools and processes being used to monitor and assess junior doctor performance could be better” [ 32 ].…”
Section: Discussionmentioning
confidence: 99%